A real-time concurrency control protocol for main-memory database systems - Ulusoy, Özgür; Buchmann, Alejandro (Information systems (Oxford), 1998)
Protocols developed so far for concurrency control in real-time database systems have assumed a dynamic acquisition of data resources as it is impossible to predict which instances of relations will actually be accessed by each transaction. In this paper ‡ ‡ A summary of the ideas presented in this paper has appeared in SIGMOD Record, Special Issue on Real-Time Databases, 25(1):23–25 (1996). , we present a new concurrency control protocol for main-memory real-time database systems, which is based on predeclaration of data requirements at a relation granularity. When a transaction is submitted, it is possible to detect with simple syntactical means which relations will be accessed by the transaction. Preacquisition of data resources enables the system to execute transactions in a conflict-free manner. The protocol also offers the possibility of determining execution times without the effects of blocking and I/O, thereby allowing us to give guarantees for the execution of high-priority transactions. Through a series of simulation experiments, the protocol is compared against some typical concurrency control protocols proposed recently for real-time database systems.